Keragaman Genetik Tanaman Bawang Merah (Allium Ascalonicum L.) Varietas Bauji Hasil Iradiasi Sinar Gamma 60Co (Generasi 5) - Widyaningtyas, Nanda Widyaningtyas; Moeljani, Ida Retno; Sulistyono, Agus (Universitas Bangka Belitung, 2023)
One of the important factors in developing new superior varieties is genetic diversity. Gamma ray irradiation of 60Co is one method of mutation induction. The aim of the study was to find out the dose of irradiation that had the best diversity value in Allium ascalonicum the Bauji variety gamma irradiation 60Co, which consisted of doses of 3 Gy and 4 Gy with 7 replications each using a Randomized Block Design (RBD). The randomization method uses the lottery draw manually. Each treatment required 56 tubers and 1 planter bag contained 4 tubers. Control plants are symbolized by the code